CORRELATION OF SEVERITY OF METABOLIC ACIDOSIS AT ADMISSION AND OUTCOME IN ASPHYXIATED NEONATES - Younus, Javaria; Hayat, Sikandar; Haroon, Farah; Waheed, Khawaja Ahmad Irfan; Khan, Mazher Qadir; Khalid, Muhammad Usman (Journal of Ayub Medical College Abbottabad, 2020)
Background: Blood gases can provide information about the perinatal, natal and postnatal condition of newborn. Severity of metabolic acidosis has deleterious effect on the outcome of babies. When the cord blood gases are not available the arterial blood gases are used for interpreting the status of newborn. The purpose of study was to determine the relationship between severity of metabolic acidosis at admission with the stage of hypoxic ischemic encephalopathy, and its outcome in asphyxiated neonates. Methods: This was descriptive cross-sectional study of 384 neonates born at ‰¥35 weeks to <42 weeks from June to December 2018, admitted in Neonatology department of the Children’s hospital & the Institute of Child Health, Lahore within first 6 hours of birth. The neonates with history of delayed cry at birth and arterial pH ‰¤7.30 and base deficit ‰¥10 were included in the study. The pH and base deficit of babies was analyzed in relation to the stage of HIE, duration of stay and death or discharge of the babies using SPSS-20. The p-value was calculated using chi-square test. Results: Total of 470 neonates were eligible. Eighty-four neonates were excluded. Finally, 384 neonates were included and analyzed for the outcome variables. With severe metabolic acidosis pH <7.01, all the babies developed HIEII/III. Majority (82.1%) of the babies expired and 27.9% had prolonged hospital stay. Conclusion: Increasing severity of metabolic acidosis at admission increases the likelihood of adverse outcome in asphyxiated neonates. Keywords: HIE; Metabolic acidosis; Base deficit; Adverse outcome